Climate change, institutional quality and SDGs: a narrative review with a focus on Yemen/ Zuhayr Khan Mustun - Mustun, Zuhayr Khan (Universiti Teknologi MARA Selangor, 2022)
The purpose of this paper is to undertake a narrative review on climate change, institutional quality, and SDGs within the context of Yemen. The methodology is a broad study of past and recent academic works related to the topic's keywords. In essence, a narrative review has been undertaken to incorporate the three interlacing issues; climate change, institutional quality, and SDG in the context of Yemen. The present research work reinforces the evidence that climate change effects are particularly more catastrophic in regions already under political, socio-economic, and cultural pressures. Eventually, the attainment of SDGs become increasingly challenging in contexts with intense climate variability and native disturbances. Besides, the lack of quality institutions and strong governance put in peril the stability of the country, thereby making it more prone to conflicts. This eventually leads to the formation of a vicious circle where low institutional quality fecund more conflicts, which in turn further destabilizes state institutions. Overall, climate change is making matters worse for countries like Yemen, and hence this study provides an insight into the Yemenite society and economy. Since this is a narrative review with an interpretive approach, further studies should aim to engage in more econometric analysis covering the interference relationships between climate change, institutional quality, and SDGs, especially in countries facing the turmoils of war and conflict.